THE MALAYSIAN SUKUK MECHANISM AS THE MOST MODERN FORM OF SUKUK RELATIONSHIP REGULATION. - Mamatmurodov Farrux Farxod o‘g‘li (World Scientific Research Journal, 2025)
Malaysia is one of the leaders in the development of Islamic financial services and is the largest sukuk market in the world. By the end of 2007, 68.9% of global sukuk, or US62 billion (RM213 billion), originated in Malaysia. In 2007, the total issuance of corporate sukuk in Malaysia exceeded RM30 billion. Leadership in the development of Malaysia’s sukuk market is not limited to volume, but also includes the introduction of innovative and competitive sukuk structures that appeal to a wider investor base. Malaysia also has a strong and comprehensive Islamic financial system based on a stable business-oriented regulatory regime and legal framework. Malaysia has become the world’s largest sukuk market, with total sukuk volume of MYR 173.5 billion as of March 2015, equivalent to 57% of the global market. The Sukuk market has become an integral part of the Malaysian capital market. Over the years, Islamic capital market products have gained global acceptance as an alternative to conventional products. There is clear evidence of acceptance of these products by non-Muslim issuers and investors. As evidence of Malaysia’s success in the Islamic capital market, 35% of all ringgit bond issuances (MYR62 billion) in 2014 were through sukuk.